Credit Market Imperfections in Middle Income Countries - Aaron Tornell; Frank Westermann (Center for Economic Studies and ifo Institute (CESifo), 2003)
In this paper we document three credit market imperfections prevalent in middle income countries that can help to explain boom-bust cycles, as well as other macroeconomic patterns observed at higher frequencies across these countries. These imperfections are: the existence of financing constraints that affect mainly the nontradables sector, currency mismatch and guarantees that cover lenders against systemic crises. In MICs T-sector firms have access to international capital markets, while most N-firms are bank-dependent and are financially constrained. Systemic guarantees generate incentives for borrowers to take on insolvency risk by denominating debt in foreign currency. This currency mismatch makes movements in the real exchange rate - the relative price between N and T goods - the driving element in the amplification of shocks.
Keywords: 330